2014
DOI: 10.1186/s12876-014-0190-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Outer membrane protein C and anti-glycoprotein 2 antibodies in inflammatory bowel disease and their association with complicated forms of Crohn’s disease

Abstract: BackgroundPrecise diagnostics of inflammatory bowel disease (IBD) and identification of potentially more aggressive phenotypes of Crohn’s disease (CD) is urgently needed. The aim of our prospective study was to assess the relationship between serum anti-OmpC IgA (Outer membrane protein C), anti-GP2 (anti-glycoprotein 2) IgG and anti-GP2 IgA antibodies with IBD and their association with complicated forms of CD.MethodsThe study included 86 patients with CD, 25 patients with UC and 45 controls, blood donors. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Interestingly, no significant difference on the correlation of anti-GP2 IgG with disease location was observed in Czech Republic CD patients. 29 Bogdanos et al revealed the association between anti-GP2 IgG with structuring behavior (B2) and perianal disease in CD patients. 17 However, no significant difference of anti-GP2 IgG with structuring behavior (B2) and perianal disease was observed in our study with Chinese CD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, no significant difference on the correlation of anti-GP2 IgG with disease location was observed in Czech Republic CD patients. 29 Bogdanos et al revealed the association between anti-GP2 IgG with structuring behavior (B2) and perianal disease in CD patients. 17 However, no significant difference of anti-GP2 IgG with structuring behavior (B2) and perianal disease was observed in our study with Chinese CD patients.…”
Section: Discussionmentioning
confidence: 99%
“…6,25 OmpC is an E. coli outer membrane protein that represents an immune response to the Enterobacteriaceae family. 32 In relation to increased risk of severe recurrence (≥ Rutgeerts i3), the total baseline quartile sum score (but not number of positive markers) was significantly greater in patients with, than patients without, severe recurrence at 18 months.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies of serologic biomarkers have found associations with disease phenotype, disease progression and disease duration [4]. ASCA, anti-OmpC, anti-I2 and anti-CBir have been associated with complicated CD, progression of disease and need of surgery, whereas the presence of pANCA has been associated with an inflammatory behaviour and a less severe disease course [18][19][20][21][22][23][24][25]. Our findings of associations between CD-related surgery and positive ASCA IgA, positive ASCA IgG and negative pANCA are therefore in line with previous studies.…”
Section: Discussionmentioning
confidence: 99%